2020
DOI: 10.1021/acs.jpclett.0c02318
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering Monitoring of Oxidation States in Defect-Engineered Two-Dimensional Transition Metal Dichalcogenides

Abstract: Recent studies have found that some transition metal dichalcogenides (TMDs) with their own defects are difficult to store in the air for a long time. Worse stability of TMDs under extreme conditions has also been reported. Therefore, monitoring the oxidation and degradation processes of TMDs can directly guide the stability prediction of TMD-based devices and monitor TMDs quality. Herein, with the case of molybdenum disulfide, UV–ozone defect engineering is used to simulate the oxidation and degradation of TMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…A-terms are the molecule HOMO to the VB edge and the VB edge to molecule LUMO charge transfer. B- and C-terms consider the coupling of photoinduced charge transfer and μ ex or μ mol by Herzberg–Teller coupling . μ ex and μ mol are charge transfers from VB to CB of NG and HOMO to LUMO of R6G, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A-terms are the molecule HOMO to the VB edge and the VB edge to molecule LUMO charge transfer. B- and C-terms consider the coupling of photoinduced charge transfer and μ ex or μ mol by Herzberg–Teller coupling . μ ex and μ mol are charge transfers from VB to CB of NG and HOMO to LUMO of R6G, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of graphene in 2004, two-dimensional (2D) layered materials have received great attention due to their unique mechanical, thermal, optical, and electrical properties. Nowadays, 2D materials (e.g., graphene and transition metal dichalcogenides) have been considered as promising candidates for next-generation SERS platforms due to their atomic uniformity, biological compatibility, seamless structure, atomic thickness, and chemical inertness. Studies have shown that CM plays a major role in the SERS of 2D materials and the fluorescence background of molecules can be effectively quenched by 2D materials. ,, However, the enhancement factor and limit of detection of 2D substrates are still not high enough, e.g., detection limit of MoS 2 is above 10 –7 M. To increase the enhancement factor of SERS for 2D materials, various defect engineering schemes are developed. For example, the MoS 2 -molecular interaction is magnified by oxygen incorporation-assisted strategies .…”
Section: Introductionmentioning
confidence: 99%
“…Glass et al reported that semiconductor-based SERS enhancements could be used as a direct method of surface oxygen vacancies concentration quantification [198]. Besides, our group reported that the oxidation process of ultraviolet-ozone-treated MoS 2 could be successfully monitored by using plasmon-free SERS technology [134]. During the oxidation process, the changes in energy bands caused by defects in MoS 2 would remarkably affect SERS.…”
Section: Chemical and Biochemical Reactions Monitoringmentioning
confidence: 93%
“…CVD techniques for the growth of monolayer MX 2 -type structures have seen a huge progress in the last few years and show remarkable results [21][22][23]. For example, a simple method to synthetize Mo-W alloyed triangular monolayers [24] with a wide range of stoichiometry morphologies has been achieved by varying CVD conditions, like the introduction of Se together with S during the growth to produce changes in the bandgap of the monolayers [25][26][27][28] and photoluminescence (PL) emission. Another technique utilizes a pre-seeding strategy, where tungsten oxide nanoparticles are used to coat the substrate surface in order to get a uniform single layer growth [8].…”
Section: Introductionmentioning
confidence: 99%
“…For both bulk and monolayer crystals, the simultaneous incorporation of chalcogen atoms like Se and S, or transition metal atoms like W and Mo, have a definitive impact on the morphology and electronic properties. It is precisely the stoichiometric ratios that determine the vibrational behavior of the layers and whose normal modes of vibration are perceptible using spectroscopic techniques [27,[33][34][35][36]. In this work, we study spectroscopic features of MoS x Se 2-x bulk crystals.…”
Section: Introductionmentioning
confidence: 99%